Penggunaan Model Jigsaw Berbantuan Media Geoboard untuk Meningkatkan Hasil Belajar Matematika - Timbul Amar Hotib (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2020)
The purpose of this research use the Jiqsaw learning model assisted by Geoboard media is to find out the steps to use the Jiqsaw learning model assisted by Geoboard Media and to improve Mathematics learning outcomes of 114340 Public Elementary School students in Tolan Week. The design of this study uses Classroom Action Research (CAR) which consists of two cycles with each cycle consisting of 3 face-to-face meetings. Learning outcomes are measured based on a written test. Increased student learning outcomes in the Coordinate Field, then the average value of students is 52.72 with 11 students who have mastery (50.50%) and 11 students who have not completed (50.50% ) of all students. Then the action was taken using Mathematics, then obtained an average value increased to 61.82 with 16 students who experienced mastery (72.73%) and 6 students who had not completed (27.27%). After learning innovation using Mathematics assisted by the jiqsaw model, the average grade value was increased to 76.36 with 19 students experiencing mastery (86.36%) and 3 students who did not complete (13.64%).